Citizen Service Centers in Kenya : The Role of Huduma Centers in Advancing Citizen-Centered Service Delivery in a Context of Devolution and Digitization - Firestone, Rachel Sohn; Schott, Berenike; Kinuthia, Muratha; Omollo, Annette (World Bank, Washington, DC, 2017)
This case study analyzes the Huduma Kenya program, under which the Government of Kenya is advancing citizen-centered public service delivery through a variety of channels, including deploying digital technology and establishing citizen service centers across the country. The paper examines key topics related to the operation, from institutional arrangements, funding, and staffing to digitization, organizational culture, and customer feedback. The program has beenparticularly successful at forging an organizational culture focused on excellence in customer service, which revolves around improving transparency, efficiency, and integrity. This organizational culture helps motivate staff and level the playing field for citizens of all backgrounds to get equal service and treatment from the same place, an important step toward enhancing accessibility and nondiscrimination. The Huduma Kenya program takes a multichannel approach, combining brick-and-mortar centers with digital service platforms to ensure that citizens with differing levels of literacy and access to the Internet are reached while still keeping pace with the latest technological developments. To date, the primary challenges encountered in the rollout of the Huduma Centers concern the coordination among the various institutions involved in their management, staffing, and oversight; and the deployment of staff incentives related to compensation and professional development.